Robust H∞ control for T–S fuzzy systems subject to missing measurements with uncertain missing probabilities - Gao, Ming; Sheng, Li; Liu, Yurong (Neurocomputing (Amsterdam), 2016)
In this paper, the robust output feedback H∞ control problem is investigated for a class of uncertain Takagi–Sugeno (T–S) fuzzy systems with missing measurements. In the underlying systems, both system parameters and missing probabilities are assumed to be effected by norm-bounded uncertainties which may reflect the reality more closely. The main purpose of this paper is to design a robust output feedback fuzzy controller such that the closed-loop system is asymptotically mean-square stable, and the disturbance rejection attenuation is constrained to a given level by means of the H∞ performance index. Sufficient conditions are established via intensive analysis for the existence of the output feedback fuzzy controller, and the corresponding solvability conditions for the desired controller gains are derived. An illustrative example is provided to show the effectiveness of the developed design method.